Experience with liver dialysis in acetaminophen induced fulminant hepatic failure: A preliminary report - Meral AKDOĞAN; Karim El-SAHWI; Urooj AHMED; Samy RASHWAN; Anthony SEBASTIAN; Harlan WRIGHT; Bakr NOUR; Ahmet GÜRAKAR (Turkish Journal of Gastroenterology, 2019)
-